2017
DOI: 10.1364/boe.8.003343
|View full text |Cite
|
Sign up to set email alerts
|

Visible spectrum extended-focus optical coherence microscopy for label-free sub-cellular tomography

Abstract: Abstract:We present a novel extended-focus optical coherence microscope (OCM) attaining 0.7 µm axial and 0.4 µm lateral resolution maintained over a depth of 40 µm, while preserving the advantages of Fourier domain OCM. Our system uses an ultra-broad spectrum from a supercontinuum laser source. As the spectrum spans from near-infrared to visible wavelengths (240 nm in bandwidth), we call the system visOCM. The combination of such a broad spectrum with a high-NA objective creates an almost isotropic 3D submicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 37 publications
4
47
0
Order By: Relevance
“…Functional extensions of OCT have made it possible to not only visualize contrasts based on backscattered intensity (reflectivity), but also motion (OCTA) [48][49][50] and polarization properties (PS-OCT) such as birefringence. [51][52][53][54] The birefringence of Aβ plaques has been studied in detail using polarimetry, [55][56][57][58] and also with PS-OCT. 59,60 The plaques appear as hyper-scattering structures in standard reflectivity OCT images, [61][62][63] but the addition of polarization-sensitive detection provides an additional tissue-specific contrast. Furthermore, the combination of PS-OCT with OCTA allows a simultaneous analysis of this tissue-specific contrast and changes in the retinal vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Functional extensions of OCT have made it possible to not only visualize contrasts based on backscattered intensity (reflectivity), but also motion (OCTA) [48][49][50] and polarization properties (PS-OCT) such as birefringence. [51][52][53][54] The birefringence of Aβ plaques has been studied in detail using polarimetry, [55][56][57][58] and also with PS-OCT. 59,60 The plaques appear as hyper-scattering structures in standard reflectivity OCT images, [61][62][63] but the addition of polarization-sensitive detection provides an additional tissue-specific contrast. Furthermore, the combination of PS-OCT with OCTA allows a simultaneous analysis of this tissue-specific contrast and changes in the retinal vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…PS-OCT visualizes amyloid-beta plaques based on their optical scattering and birefringent properties [33][34][35][36]. Previous studies mainly exploited the hyperscattering characteristics of plaques and only one report investigated the birefringent characteristics of neuritic plaques using PS-OCT [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports have demonstrated that amyloid-beta plaques in both human and mouse brain tissue can be visualized using either conventional OCT, PS-OCT [19,[32][33][34][35][36] or other functional extensions such as spectroscopic OCT [32] or directional OCT [36]. Label-free imaging of cerebral amyloid-beta plaques has been achieved using extended-focus optical coherence microscopy (OCM) in the near infrared range at 800 nm [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With few exceptions [1012], conventional flying-spot OCT and OCM systems use a symmetric confocal imaging geometry, where the detection path retraces the illumination path, resulting in identical illumination and detection point spread functions (PSFs). While such a configuration facilitates optical alignment, this strategy has disadvantages.…”
mentioning
confidence: 99%